PENGARUH LARGE BOOK-TAX DIFFERENCES TERHADAP PERSISTENSI LABA, AKRUAL DAN ARUS KAS PADA PERUSAHAAN MANUFAKTUR DI BEI - MELITA NOVIANA SIN (Universitas Katolik Widya Mandala Surabaya, 2012)
Quality earnings are earnings which may reflect the continuation of future earnings, which is determined by the components of accruals and cash flows. Book-tax differences may represent the management discretion in the accrual process to assess the quality of earnings. Persistence of earnings is one component of the predictive value of earnings and also the element of relevance that some information in the book-tax differences may affect the persistence of earnings. This study aims to examine the effect of large book-tax differences on the persistence of earnings, accruals and cash flows compared to firms with small book-tax differences and earnings persistence effect on investor expectations especially for the persistence of accruals on each sub-sample of book-tax differences. Object of study is a manufacturing company listed on the Stock Exchange in 2008-2009 with a sample of 37 manufacturing companies selected by purposive sampling technique. The results showed firms with large negative book-tax differences have persistence of the accrual component of earnings that are not much different from the firms with small book-tax differences and not proven that the stock price could reflect the persistence of earnings, accruals and cash flows but investors tend to be pessimistic about the current earnings in relation to future earnings in other words, earnings is considered to have low persistence for all sub-sample of book-tax differences.